Considering human challenge trials for tuberculosis vaccine development. Issue 2 (21st January 2022) - Kleinwaks, Gavriel; Schmit, Virginia; Morrison, Josh
Abstract: Human challenge trials provide a promising route to cut down on the high, sometimes prohibitive, costs of vaccine development. By requiring fewer participants than a conventional clinical trial and reducing the time required for a trial, human challenge trials improve economic feasibility and reduce the risk of vaccine development. Tuberculosis is one disease where challenge trials could be very impactful, given that it is a widespread and dangerous disease that is nonetheless difficult to track in a standard clinical vaccine trial. Various attenuated strains of Mycobacterium tuberculosis are in development and can be used in a challenge trial in order to reduce the risk to challenge trial participants and their surrounding communities.